The child's right to maintenance: the extent of the family's responsibilities in Islamic law and according to the family law provisions of Muslim countries - Hj Ibrahim, Badruddin; Mohd, Azizah (Brill Academic Publisher, 2011)
The relationship between parents and children is a strong, ineluctable one. It has a profound, emotional effect on both, as it is based on blood and lineage. The child-parent relationship gives rise to mutual rights and duties. These rights relate to the person of the child: for protection, care and maintenance. This article will examine the rights of children to maintenance. It will examine the law applied in Malaysia and several Muslim countries: Morocco, Jordan, Syria, Kuwait and Qatar. It will identify the family relationships which have particular responsibility to provide maintenance to children, and examine the extent of the obligation, and the entitlement of children to such rights. This article also aims to investigate the extent of the role of family law institutions in safeguarding such rights of children. Where appropriate, it will make suggestions for the improvement of relevant Islamic statutory provisions in Malaysia.